Pencegahan primer dan perilaku sehat pada setiap anggota keluarga yang tidak menderita diabetes melitus di dalam keluarga dengan diabetes melitus - Gina Ratna Suminar; Citra Windani Mambang Sari; Iwan Shalahuddin (Holistik Jurnal Kesehatan, 2020)
The Primary prevention and healthy lifestyles among non diabetic members of familial type 2 diabeticBackground:  Diabetes Mellitus (DM) is one of the diseases that tends to have the increasing rate of incidence. DM can be prevented through preventive and mitigating measures of risk factors that can cause DM, especially in someone who has a history of DM on family members.Purpose: Describing the primary prevention and healthy lifestyles among non diabetic members of familial type 2 diabetic at Public Health Centre (Puskesmas) the work area of Tarogong, west Java Indonesia.Methods: A quantitative descriptive with consecutive sampling which was conducted on 138 respondents from the population of 210 family members of patients with DM. Data collection techniques were conducted by using questionnaires to find out and measure DM prevention by healthy lifestyles. The data are grouped into categories of good and poor that were analyzed using descriptive statistics based on the mean value of the questionnaire.Results: Finding that all respondents (88.4%) was in good category in DM prevention by healthy lifestyles. While the behavior of prevention of DM seen from the diet most of the respondents are in good category (61.6%), physical activity almost entirely in good category (91.3%), weight control mostly in category poor (55.1%), smoking habit almost entirely in category (86.2%), and stress management is almost entirely in good category (87.7%).Conclusion: The small percentage of respondents are still lacking of the information about DM, thus becoming poor aware of the importance in doing DM prevention behavior by healthy lifestyles. This happens because most of the respondents have not yet received the necessary information about DM disease. Therefore, it is recommended that the Public Health Centre (Puskesmas) or other local facilities provide information about DM disease not only to the patients but also to their family members.Keywords: The Primary Prevention; Healthy Lifestyles; Type 2 DiabeticPendahuluan: Diabetes Melitus (DM) merupakan salah satu penyakit yang memiliki angka kejadian terus meningkat. DM dapat dicegah melalui tindakan pencegahan dan penanggulangan dari faktor resiko yang dapat menyebabkan DM. Resiko DM lebih besar terjadi pada anggota keluarga yang mempunyai riwayat DM.Tujuan: Mengidentifikasi gambaran perilaku pencegahan primer pada anggota keluarga dengan DM di wilayah kerja Puskesmas Tarogong.Metode: Deskriptif kuantitatif dengan menggunakan consecutive sampling yang dilakukan pada 138 responden dari jumlah populasi 210 anggota keluarga penderita DM. Teknik pengumpulan data dilakukan dengan menggunakan kuesioner untuk mengukur perilaku pencegahan DM serta data dikelompokkan ke dalam kategori baik dan buruk yang dianalisis menggunakan statistik deskriptif berdasarkan nilai mean kuesioner.Hasil: Didapatkan hampir seluruhnya responden (88.4%)  berada pada kategori baik dalam perilaku pencegahan DM. Sedangkan perilaku pencegahan DM dilihat dari pola makan sebagian besar responden berada pada kategori baik (61.6%), aktivitas fisik hampir seluruhnya pada kategori baik (91.3%), pengontrolan berat badan sebagian besar pada kategori buruk (55.1%), kebiasaan pengendalikan perilaku merokok hampir seluruhnya pada kategori baik (86.2%), dan pengelolaan stres hampir seluruhnya pada kategori baik (87.7%).Simpulan: Sebagian kecil responden masih buruk dalam melakukan perilaku pencegahan DM. Hal ini terjadi karena sebagian besar responden belum semuanya mendapatkan informasi tentang penyakit DM. Disarankan agar pihak Puskesmas dapat memberikan informasi mengenai penyakit DM tidak hanya pada pasien yang menderita tetapi anggota keluarganya pun perlu diberikan.